HYDROLOGICAL ROLE OF FOREST COVER OF PRECARPATHIAN REGION - Oliynyk, V. S.; Tkachuk, O. M. (Forestry and Forest Melioration, 2018)
Annual parameters of components of water balance, rain flooding, spring floods and ice phenomena on the columbines of Precarpathian region are characterized with forest cover change from 21 to 59 percent. Its influence on annual regime of rivers is analyzed. The role of forest in prevention of solid overburden flow is estimated. It is found out that forest cover doesn't demonstrate notable influence on moisture and water resources on the background of essential variety of natural conditions of the research region. Empirical dependences of indicators of groundwater inflow and natural river control from the river basins’ forest cover are obtained.